(untitled) (Journal of Politics and International Studies, 2023)
Afghanistan has been at a focal point for great powers especially United States after cold war era due to its strategic location. It has been unfortunate for Afghanistan that the country has been a constant victim of proxy wars after 9/11 till date. Pakistan, being Afghanistan‟s neighboring country is having a direct demeanor when it comes to security matrix concern which requires Pakistan to play its role in such precarious situation by not only mediating but by highlighting the failed role of international humanitarian organizations for ensuring regional security of South Asia and particularly of these countries. The international humanitarian laws which were made to protect the lives of human beings all over the world, has fathomed to be failed. The paper has implemented the theory of Barry Buzan and Ole Weaver‟s framework of “regional security complex”, since all the states are interdependent, then the regional security over the anarchic international system has become far from uniform. In the end, the role of Pakistan will be critically analyze that whether Pakistan has been successful or not when it comes to playing the role of a mediator or helping in derailing down the extremism factor in Afghanistan in context of political, social and economic instability. This paper has addressed the research questions that how foreign invasion can create regional security threats not only to the targeted country but whole region is directly affected with it. The research is qualitative and descriptive in which effects of independent variables of foreign policy of Pakistan as a mediator, role of humanitarian organization under United Nation and intervention of United States has been studied on the dependent variable of stability in Afghanistan.